Live Donor Assessment Tool (LDAT): A Turkish validity and reliability study - Duman, Berker; Herdi, Oğuzhan; Sayar-Akaslan, Damla; Kırımker, Elvan Onur; Çolak, Burçin; Ağtaş-Ertan, Ece; Çakar, Gülsüm; Hasanlı, Jamal; Kocaay, Akın Fırat; Tüzüner, Acar; Koloğlu, Meltem; Karayalçın, Kaan; et al. (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Psychosocial and psychiatric evaluations are crucial components of the assessment of a live donor candidate. The Live Donor Assessment Tool (LDAT) was developed for this purpose. This study aims to evaluate the validity and reliability of the Turkish version of LDAT. Materials and Methods: 132 live kidney or liver donor were referred to assess their psychosocial/psychiatric appropriateness for donation and were randomized for clinical evaluation as usual or with LDAT. The internal consistency of LDAT was measured by Chronbach’s alpha coefficient. Inter-rater reliability was measured by using Spearman’s correlation coefficient. The potential validity of LDAT was assessed by comparing LDAT scores to clinical decisions. The Mann-Whitney U test was used to compare LDAT scores across two clinically classified groups (acceptable/declined). Logistic regression was performed using LDAT scores to predict the clinical decision. Results: The Turkish version of LDAT items demonstrate good internal consistency (α=0.773). Inter-rater reliability of LDAT demonstrated strong correlation (ICC=0.72). LDAT scores differentiated the accepted/declined groups, and strongly predicted the clinical decision. With a cut-off score of 60.5, LDAT was found to have high sensitivity and specificity. Conclusion: The Turkish version of LDAT was found to be a valid and reliable tool. LDAT could be an appropriate tool to assess live donor candidates.